Urgensi Kenyamanan Belajar dan Mengajar dalam Islam Serta Kaitannya dengan Al-Qur???an Surat Al-Mudallah Ayat 11 - Purmansyah Ariadi; Rulitawati; Antoni (At-Tahfidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2021)
Learning and teaching activities are processes of activities carried out by humans, both formal and non-formal learning activities, because Islam teaches that humans are obliged to study. In this study, the writer wants to reveal the relationship between the convenience of learning and teaching in Islam and the connection with the Al-Qur'an Surah Al-Mujadalah verse 11, where this urgency discusses and interprets the verse in terms of comfort in the learning and teaching process. Research carried out by the library and the methods used by the Research Library by looking for sources related to education and interpretations related to education. The results of this study, the convenience of the teaching and learning process carried out by educators, is closely related to the environment, facilities and infrastructure, which support teaching and learning activities, the results obtained by the interaction of teachers and students will be better, both the relationship and the relationship with the comfort of learning and teaching. with Al-Qur; an surah Al-Mujadalah verse 11, learning is very important for human life, based on the three interpretations of the Qur'an it is concluded that Allah will raise the rank of those who believe and have knowledge.